Pengembangan E-LKPD Berbasis Guided Inquiry Terintegrasi Etnokimia Menggunakan Liveworksheets Pada Materi Laju Reaksi - Muthia, Kesya Zahra; Erviyenni, Erviyenni; Haryati, Sri (Jurnal Pendidikan Kimia Universitas Riau, 2025)
This research aims to produce a valid E-LKPD and find out the user response to the developed E-LKPD. This research is designed using development research with a 4-D development model consisting of four stages, namely define, design, develop, and disseminate. However, this research was only carried out until the development stage. Research instruments in the form of validation sheets and user response sheets. The instruments used are validation sheets and user response sheets. Validation is carried out by two material expert validators and one media expert validator, and user responses are obtained from teachers and students. The results of the validation of the material based on the aspect of content feasibility, the characteristics of the Guided Inquiry integrated with ethnochemistry, presentation, linguistics, and graphics in a row, namely 95.31%; 97,91%; 96,87%; 93,75%; and 90,62% with valid categories. Media validation results are based on aspects of E-LKPD size, E-LKPD cover design, and E-LKPD content design with 100%; 93,75%; and 95% with valid categories respectively. User response test results were obtained with an average score of 95.83% by chemistry teachers with very good criteria and 91.44% by students with very good criteria.